THE ROLE OF DIGITAL INFLUENCERSIN THE ACTIVITY OF PUBLIC RELATIONS AND MARKETING ON SOCIAL MEDIA IN INDONESIA - Hakim, Atikah Kanza Atsarina (UNIVERSITAS PAKUAN, 2023)
This study aims to discover the role of digital influencers in the activity of public relations and marketing on social media in Indonesia. Today, many companies use digital influencers to spread positive information about their product. This is because social media has brought changes in several aspects, even the practice of public relations. The method used in this research is a literature review with a qualitative approach. According to the topic, the data was obtained from previous studies gathered from every source, such as Google Scholar and the website library of The University of Indonesia. The data was collected in the form of journals, articles, and books. After collecting the data, the data was analysed focusing on the keywords which are the main topic of the study. The result of this study shows that the digital influencer does not have a significant influence on the public’s purchase intention in Indonesia. However, the activity of digital influencers that relates to a certain brand on social media has a positive and significant effect on the local cosmetic brand image and the consumers’ self-concept. In addition, even though the digital influencer has the role to introduce a product at the entry level, by giving out basic information about the product to the society or the prospective consumers, it is also discovered that the digital influencer has a role to promote new stuff that the society needs to know.